The Effect of Financial and Non-Financial Factors on Audit Report Lag - Yasmin Afra Azizah; Yuneita Anisma; Riska Natariasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
The timeliness of financial reports is a key issue in accounting due to the frequent delays in audited financial reports, which can reduce stakeholder confidence in the information provided. Research on audit report lag is an essential area of study to understand the factors that affect the duration of audit reporting as a whole, as the timeliness of audit reports is important in providing relevant information for decision-making. This study aims to determine the effect of profitability, leverage, audit opinion, auditor switching, and public accounting firm size on audit report lag. The study population consists of property & real estate companies listed on the Indonesia Stock Exchange (IDX) under the IDX-IC classification during the period 2021-2023. The sample consists of 34 companies selected using purposive sampling. The analysis method used in this study is multiple linear regression. The results of this study indicate that the profitability variable affects audit report lag, the leverage variable does not affect audit report lag, the audit opinion variable affects audit report lag, the auditor switching variable does not affect audit report lag, and the audit firm size variable does not affect audit report lag.